A comprehensive review on synthesis of pristine and doped inorganic room temperature stable mayenite electride, [Ca24Al28O64]4+(e−)4 and its applications as a catalyst. (June 2019) - Khan, Karim; Tareen, Ayesha Khan; Aslam, Muhammad; Thebo, Khalid Hussain; Khan, Usman; Wang, Renheng; Shams, S. Saqib; Han, Zhang; Ouyang, Zhengbiao
Abstract: Advances in the device fabrication in all emerging fields with promising features and improved control on material properties provide a strong motivation for researchers to reveal, recognize the potential of existing materials and to develop new ones with excellent properties by scheme a low cost syntheses method. Since the discovery of abundant, inorganic mayenite electride, [Ca24 Al28 O64 ] 4+ (e − )4 (thereafter, C12A7:e − ) (2003), it has attracted much attention due to its unique and unconventional properties such as high electron concentration (∼2.3–7 × 10 21  cm −3 ) and low work function (WF∼2.4 eV), which are comparable value with alkali metals, but is chemically inert in an ambient atmosphere. Furthermore, a severe reducing environment enables us to substitute electrons almost completely for anions in the cages, forming a stable inorganic electride, C12A7:e − . Finally, the formation of these active anions in this material has potential application as a catalyst support in the NH3 synthesis/decomposition, CO2 dissociation and specially recently introduced by our group as electrocatalyst in fuel cell. To further boost these applications the important thing was to synthesize high specific surface area, nanosized C12A7:e − powder with enhanced conductivity, that can be done by cation doping. Over the last decade, experimental studies supported by theoretical calculations have demonstrated that cation elements doping can further boost its electrical properties. Therefore, our group studied doping with more suitable cations, Si, Sn, Ga, V etc in C12A7:e − and we will explain each in detail. In this review we are going to describe progress in the synthesis of C12A7:e − especially in nanosized powder material, and about most important recent challenges towards the suitable cations doping in C12A7:e − electride and finally its industrial important applications as a catalyst.